Genetic characterization of a novel picornavirus in Algerian bats: co-evolution analysis of bat-related picornaviruses - Zeghbib, Safia (Sci Rep, 2019)
Bats are reservoirs of numerous zoonotic viruses. The Picornaviridae family comprises important pathogens which may infect both humans and animals. In this study, a bat-related picornavirus was detected from Algerian Minioptreus schreibersii bats for the first time in the country. Molecular analyses revealed the new virus originates to the Mischivirus genus. In the operational use of the acquired sequence and all available data regarding bat picornaviruses, we performed a co-evolutionary analysis of mischiviruses and their hosts, to authentically reveal evolutionary patterns within this genus. Based on this analysis, we enlarged the dataset, and examined the co-evolutionary history of all bat-related picornaviruses including their hosts, to effectively compile all possible species jumping events during their evolution. Furthermore, we explored the phylogeny association with geographical location, host-genus and host-species in both data sets.